ANALYSIS OF THE ACADEMIC PRODUCTION OF THE GTT SCHOOL OF CBCE (Fiep Bulletin - online, 2014)
Objectives to identify the scientific nature of the production and publication in the oral communication of GTT: School, of the COMBRACEs of 1997, 1999, 2001 and 2003. The initiative justify itself by the scientific contribution that makes possible comprehend the uses of the theories and its relations with the study objects of the authors of GTT. The study delimited to the method of documental research, analyzing 111 articles. In the realized raisings in the annuals of the CONBRACEs, we identified the themes that had more frequency in the articles of the authors that published in the GTT:School. Also evidences the presence of education theory matrixes, as of other areas of scientific knowledge and the difficulties of using this theories by some of the authors. The theories found in the articles were: Cultural Anthropology; Motor Learning; Phenomenology; History of Scholar Disciplines; History of the Curriculum; Constructivist Theory; Critic Theory; Curricular Critic Theory; Developmentist Theory; Human Development Theory; Critic history Theory; Theory of the Game; Theory of Human Motricity; Post-Critic Theory and Theory of Social Representations.
Keywords: Objects; Physical Education; Theory Matrixes